Odpowiedzi

  • Użytkownik Zadane
2009-12-14T15:26:02+01:00
A= 2 - √3 i b= 3 + 2√3


a-b
2 - √3 - 3 + 2√3
-1+√3

a x b
(2-√3)x(3+2√3)
6+4√3-3√3-2√9
6+4√3-3√3-6
√3

a/b mi wyszlo ale zle chyba


1/a
1/ 2-√3
2+√3/(2-√3)(2+√3)
2+√3/4-3
2+√3/1



(3+2√3)²
9+12√3+12
21+12√3
Najlepsza Odpowiedź!
2009-12-14T15:48:12+01:00
A= 2 - √3
b= 3 + 2√3

a-b
2 - √3 -3 + 2√3= -1+√3

axb
(2 - √3) x(3 + 2√3)= 6+4√3-3√3-6=√3

a/b
2 - √3/ 3 + 2√3 x 3-2√3/3-2√3= 6-4√3-3√3+6/9-6√3+6√3-12= -7√3/-3

1/a
1/2 - √3 x 2 + √3/2 + √3= 2+√3/4+2√3-2√3-3= 2+√3

b²= (3 + 2√3)²=9+12√3+12= 21+12√3